2013
DOI: 10.1016/j.celrep.2013.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent Stem Cell Protein Sox2 Confers Sensitivity to LSD1 Inhibition in Cancer Cells

Abstract: Gene amplification of Sox2 at 3q26.33 is a common event in squamous cell carcinomas (SCCs) of the lung and esophagus, as well as several other cancers. Here, we show that the expression of LSD1/KDM1 histone demethylase is significantly elevated in Sox2-expressing lung SCCs. LSD1-specific inhibitors selectively impair the growth of Sox2-expressing lung SCCs, but not that of Sox2-negative cells. Sox2 expression is associated with sensitivity to LSD1 inhibition in lung, breast, ovarian, and other carcinoma cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
125
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(136 citation statements)
references
References 39 publications
5
125
0
Order By: Relevance
“…LSD1 and its inhibitor have been reported to target cancer stem cell markers in several cancers (Wang et al 2011;Zhang et al 2013;Amente et al 2013). Our study revealed that LSD1 is involved in CRC tumorigenesis by up-regulating the expression of LGR5, a functional CRC stem cell marker, which had been confirmed to promote cancer stemness in CRC cells in our previous study .…”
Section: Discussionmentioning
confidence: 99%
“…LSD1 and its inhibitor have been reported to target cancer stem cell markers in several cancers (Wang et al 2011;Zhang et al 2013;Amente et al 2013). Our study revealed that LSD1 is involved in CRC tumorigenesis by up-regulating the expression of LGR5, a functional CRC stem cell marker, which had been confirmed to promote cancer stemness in CRC cells in our previous study .…”
Section: Discussionmentioning
confidence: 99%
“…SOX2 amplification was detected in SQCC of lung and esophagus, and is required for survival of SQCC cell lines [209]; an NGS study [4] identified SOX2 amplification in 21% of lung SQCC. Histone demethylase LSD1/KDM1 was found to be significantly elevated in Sox2-expressing SQCC, and inhibition of LSD1 with selective inhibitor CBB1007 had a cytotoxic effect on cell lines with SOX2 amplification [210]. LSD1 specifically demethylates histone H3K4.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore in the present study, we examined the effect of LSD1 on cell migration and invasion using LSD1-knockdown and LSD1-mediated epigenetic modification contributes to ovarian cancer cell migration and invasion Plasmid constructions and transfections. For generation of the shRnA-LSD1 plasmid, annealed short hairpin oligonucleotides (the RnAi Consortium collection TRCn0000046072; Sigma-Aldrich) targeting CCACgAgTCAAACCTTTATTT in the coding regions (CDS) of LSD1 were cloned into pLKO-Tet-On by AgeI and EcoRI sites to produce pLKO-Tet-On-shLSD1 as described previously (30,31). The constructs were confirmed by DnA sequencing.…”
Section: Introductionmentioning
confidence: 99%